Предмет: Математика,
автор: angelovamari
Решите уравнение: 6-3(х+1)=7-х
Ответы
Автор ответа:
0
6-3(х+1)=7-х
6-3х-3=7-х
-3х+х=7+3-6
-2х=4
х=-2
6-3х-3=7-х
-3х+х=7+3-6
-2х=4
х=-2
Автор ответа:
0
Спасибо!
Автор ответа:
0
6-3(x+1)=7-x
6-3x-3=7-x
-3x+x=7-6+3
-2x=4
-x=4^2
-x2
6-3x-3=7-x
-3x+x=7-6+3
-2x=4
-x=4^2
-x2
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: Обществознание,
автор: buriamw0152
Предмет: История,
автор: vanekkmus
Предмет: Литература,
автор: sofia0682
Предмет: Математика,
автор: екатерина080808
Предмет: Химия,
автор: jegte